The role of internet addiction and mastery motivation on academic achievement among school‐aged children - Ferdowshi, Nafiza; Shithee, Ummee Habiba (Dhaka University Journal of Biological Sciences, 2018)
The purposes of the present study were to investigate association of internet addiction and mastery motivation with academic achievement of school-aged children and to investigate whether there is any significant difference of internet addiction and mastery motivation according to grade of school-aged children. Three hundred participants were selected from different grade levels (VIII, IX, X). The collected data were analyzed by using Pearson product moment correlation and one-way ANOVA. Results showed that mastery motivation was positively correlated with academic results that was significant. On the other hand, negative relationship between the academic results of children with internet addiction which was not significant. The findings also revealed that both internet addiction and mastery motivation had significant difference with different grade levels of children. Study limitations and further implications were also discussed. Dhaka Univ. J. Biol. Sci. 27(1): 49-56, 2018 (January)